2019
DOI: 10.3126/ijasbt.v7i2.23973
|View full text |Cite
|
Sign up to set email alerts
|

Fodder Production and Livestock Rearing in Relation to Climate Change and Possible Adaptation Measures in Manaslu Conservation Area, Nepal

Abstract: A study was conducted to find out the production potential, nutrient composition, and the variability of the most commonly available fodder trees along with the varying altitude to help optimize the dry matter requirement during winter lean period. The study was carried out in Lho and Prok Village Development Committee of Manaslu Conservation Area (MCA), located in Gorkha district of Nepal.The study was conducted in two parts: social and biological. Accordingly, a households (HHs) survey was conducted to colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…Changing of feed resources based on availability and cost, purchasing of feed ingredients in bulk, using crop/food wastes, harvesting of forages growing naturally in open access lands and reducing herd size were strategies used for coping with feed scarcity among urban and peri-urban livestock farmers in Kampala, Uganda [48]. The fact that respondents in the current study destocked their animals as coping strategy to feed scarcity concurs with that of Dhakal et al [49] who observed that farmers in Nepal reduced their livestock during feed scarcity. The results of the study suggest the need for improving the utilization of locally available conventional and non-conventional feed resources, grazing land management, adoption of rotational grazing, feed conservation (hay and crop residues), supplementation of poor quality crop residues and dry natural pastures, improving crop residues quality, forage cultivation where land is not a limit or integration with cereal crops for providing feed for animal, and food and fuel wood for humans without reducing land for crop production seems to be essential intervention for coping with dry season feed scarcity.…”
Section: Feed Shortages and Coping Strategiessupporting
confidence: 80%
“…Changing of feed resources based on availability and cost, purchasing of feed ingredients in bulk, using crop/food wastes, harvesting of forages growing naturally in open access lands and reducing herd size were strategies used for coping with feed scarcity among urban and peri-urban livestock farmers in Kampala, Uganda [48]. The fact that respondents in the current study destocked their animals as coping strategy to feed scarcity concurs with that of Dhakal et al [49] who observed that farmers in Nepal reduced their livestock during feed scarcity. The results of the study suggest the need for improving the utilization of locally available conventional and non-conventional feed resources, grazing land management, adoption of rotational grazing, feed conservation (hay and crop residues), supplementation of poor quality crop residues and dry natural pastures, improving crop residues quality, forage cultivation where land is not a limit or integration with cereal crops for providing feed for animal, and food and fuel wood for humans without reducing land for crop production seems to be essential intervention for coping with dry season feed scarcity.…”
Section: Feed Shortages and Coping Strategiessupporting
confidence: 80%
“…The dry matter and ash contents were significantly varied among the altitudes. Dhakal et al [44] also reported that dry mater and ash contents of Melia azadarch, Morus alba, Ficus roxburghii, and Ficus nemoralis were significantly varied among the altitudes. Potassium, calcium, crude protein, and starch increased significantly in C. australis foliage with increasing altitude, whereas, dry matter, phosphorus, and soluble sugars decreased with increasing altitude in C. australis foliage (Table 2).…”
Section: Discussionmentioning
confidence: 97%
“…This In Nepal's forage production sector, maintaining proper irrigation in accordance with plant requirements is a constant challenge [1], [2]. The problems are primarily present in major cereals, and minor crops like oat and other seasonal forages are experiencing the same problems [3].…”
Section: Introductionmentioning
confidence: 99%